The European Integration Crisis An Economic Analysis. - Loužek, Marek (Cambridge Scholars Publisher, 2020)
European integration is not a priori positive or negative: it results from the interaction between various interests. During the past few years, however, it has been impossible to ignore increasingly strident claims that the European Union is in the midst of a crisis. According to this perspective, European institutions do not function well, democracy in the Union is flawed, eurozone problems have reached a critical point, and inward migration, which European institutions seem incapable of handling, is escalating.This book demonstrates that public choice theory can be a suitable analytical too.